Strategic Development of Economic Innovation Management for Sustainable Organizational Performance - Agis Ahmad Rodiansjah; Agus Rohmat Hidayat; Nur Alifah; Kyra Kholilah Wardaniyah (Journal of Management Economic and Financial, 2025)
This study investigates the strategic development of economic innovation management as a driver of sustainable organizational performance, synthesizing theoretical frameworks and empirical evidence from recent Scopus-indexed research. Economic innovation management encompassing financial, digital, and institutional dimensions has become a critical determinant of organizational resilience in an era of accelerating globalization, digitalization, and environmental regulation. Employing a mixed-methods approach that integrates a systematic literature review, a conceptual model, and a composite Innovation-Sustainability Performance Index (ISPI), this article identifies five strategic dimensions: (1) digital transformation and green innovation, (2) financial optimization and investment efficiency, (3) governance and stakeholder alignment, (4) human capital and knowledge management, and (5) circular economy and supply chain integration. Empirical analysis across 104 selected high-impact studies reveals a statistically significant positive relationship (r = 0.74, p < 0.001) between innovation management sophistication and sustainable performance indicators. The proposed ISPI model allows organizations to benchmark their innovation trajectories and diagnose strategic gaps. Policy implications and managerial recommendations are presented for practitioners and policymakers seeking to foster long-term value creation within sustainability-oriented frameworks.